Private international law and arbitration. - Coe, Jack J., 1953-; Childress, Donald Earl, 1975- (Private international law ;, 2018)
This groundbreaking research review analyses leading work at the intersection of private international law and arbitration. Written by two recognised experts in the field, it covers wide range of topics, from international arbitration agreements and choice of law to the enforcement of awards and arbitration involving states. This authoritative study provides an essential research resource for students, academics and practitioners alike.